Global Changes in the Epidemiology of Community-Acquired Pneumonia - Wiemken, Timothy L.; Peyrani, Paula; Ramirez, Julio A. (Seminars in Respiratory and Critical Care Medicine, 2012)
Lower respiratory tract infections are the most common infectious cause of death in the world and the third most common cause of death globally (all causes). This article reviews the epidemiology of community-acquired pneumonia from a global perspective. Major areas of epidemiological work include (1) disease surveillance to define the burden of disease and to document outbreaks, (2) identification of risk factors for a disease to optimize prevention strategies, and (3) comparisons of treatment effects to improve clinical outcomes for patients with the disease.
Keywords: community-acquired pneumonia (CAP); epidemiology; risk factors; prevention; treatment